A new karst-dwelling, colorful pitviper (Viperidae: Trimeresurus) from northern Peninsular Thailand - Sumontha, Montri; Suntrarachun, Sunutcha; Pauwels, Olivier S. G.; Pawangkhanant, Parinya; Chomngam, Nirut; Iamwiriyakul, Prapanth; Chanhome, Lawan (Zootaxa, 2021)
We describe a colorful and distinctively patterned, karst-dwelling pitviper, Trimeresurus kuiburi sp. nov., from the isolated, coastal massif of Khao Sam Roi Yot in Kui Buri District, Prachuap Khiri Khan Province, in northern Peninsular Thailand. The new species, member of the ‘Cryptelytrops group’ sensu Malhotra & Thorpe (2004) and morphologically and genetically allied to Trimeresurus kanburiensis and T. venustus, differs from all pitviper taxa by a combination of red/purple bands on a green dorsum; a white concave suborbital stripe in males (straight and less visible in females); white, spaced vertebral dots in males (absent in females); pale green belly lacking dark dots or stripe on the lateral sides of the ventrals; partially fused first supralabial and nasal scale; 19 dorsal scale rows at midbody; 164–171 ventrals; 63–65 subcaudals in males, 51–53 in females; maximal known SVL of 451 mm; and long, papillose hemipenes.